IMMU-10. INTERIM ANALYSIS OF THE HIT-HGG REZ IMMUNVAC STUDY - DENDRITIC CELL VACCINATION WITH PARTIAL TREG DEPLETION IN CHILDREN, ADOLESCENTS, AND ADULTS WITH RELAPSED HIGH-GRADE GLIOMAS. (4th December 2020) - Eyrich, Matthias; Krauss, Jürgen; Rachor, Johannes; Monoranu, Camelia; Bison, Brigitte; Löhr, Mario; Rückriegel, Stefan; Wölfl, Matthias; Miller, Elisabeth; Schlegel, Paul G; Kramm, Christof
Abstract: Efficacy of therapeutic dendritic cell vaccines (DCV) can be limited by immunosuppressive mechanisms in the micromilieu of high-grade gliomas. In the HIT-HGG-Rez Immunovac trial (Eudra-CT 2013-000419-26), we investigate whether a reduction of Treg with metronomic cyclophosphamide (metrCyc) might be a feasible option to improve vaccine efficacy. 10 pediatric (mean age 11.4±4.2y) and 5 adult patients (mean age 39.5±19.9y) with relapsed glioblastoma were treated according to the HIT-HGG-Rez Immunovac protocol so far. 2 children were treated within the trial, the other 13 in the pilot phase. Patients received upfront oral metrCyc for 2–4 weeks. After reoperation and monocyte-apheresis, patients received 4 weekly intradermal doses of autologous, TNFa/IL-1ß matured DCs pulsed with tumor lysate in imiquimod-prepared skin. Thereafter, tumor lysate boosts were given. All patients received at least 5 vaccines (4xDCs, 1xlysate boosts). MetrCyc was well tolerated and led to a reduction in Treg-frequency of 35.6±17.8% followed by a rebound after cessation of metrCyc. Importantly, 13/14 analyzed patients showed a positive IFNg-T-cell response against autologous tumor lysate with a tendency to decrease over time. 6-month overall survival was 100%, compared to 65% in a historical control. Mean PFS and OS were 5.7 and 21.1 months with no difference between adults and children. We conclude that DCV in combination with partial Treg depletion is feasible, safe, and related with a high rate of tumor-specific IFNg-responses. As the clinically and immunologically beneficial effects seem to diminish over time, we aim to combine our approach with checkpoint inhibition in the next amendment.